Cobrotoxin, a single peptide from snake venom, ameliorates atopic dermatitis via suppression of MK2 modulated by IgE and IL-33 - Lee, Jin Woo; Choi, Younghoon; Lee, Sang Heon; Park, No-June; Hadiwidjaja, Mediana; Sohn, Young Chang; Jufri, Nurul Farhana; Sohn, Eun-Hwa; Kim, Su-Nam (대한독성 유전단백체 학회, 2025)
BackgroundAtopic dermatitis (AD) is a prevalent chronic inflammatory skin disease, causing significant impairment in daily life. It typically results from the compromised skin barriers and induces the Th2-dominant immune responses, which is heavily influenced by Interleukin-33 (IL-33). Meanwhile, snake venom has been known to be effective for various medical treatments. But, its role and mechanism in AD treatment are yet to be explored.ObjectiveThis study aimed to explore the therapeutic potential of cobrotoxin (CoTX), a single peptide from snake venom, in treating allergic AD via in vitro and in vivo models.ResultsPurified CoTX inhibited degranulation in RBL-2H3 cells, a marker for allergic inflammation. It reduced IgE secretion from B cells and modulated IL-33 expression in keratinocytes. CoTX effectively regulated both allergic and pseudoallergic pathways, suggesting its suppressive control over early and late stages of allergic reactions. The study also investigated CoTX's impact on the IL-33 receptor ST2 and associated signaling proteins. The result was that CoTX inhibited IL-33- and IgE-induced activation, phosphorylation of MK2, and transactivation of NF-kappa B. In a DNCB-induced AD mouse model, CoTX treatment significantly improved AD symptoms and reduced epidermal thickness and mast cell infiltration. Finally, CoTX lowered serum IgE and IL-4 levels.ConclusionThe study suggests that CoTX has anti-allergic and anti-inflammatory effects in allergic AD. By targeting IL-33 and IgE pathways, CoTX demonstrated potential in regulating mast cell activation and inflammatory cytokine production. The observed improvements in the AD mouse model indicate CoTX as a promising candidate for further research towards developing effective and safe treatments for AD.